2006
DOI: 10.1254/jphs.scj05006x
|View full text |Cite
|
Sign up to set email alerts
|

Generalization of NMDA-Receptor Antagonists to the Discriminative Stimulus Effects of κ-Opioid Receptor Agonists U-50,488H, but Not TRK-820 in Rats

Abstract: Abstract. Generalizations of NMDA-receptor antagonists to the discriminative stimulus effects of κ-opioid receptor agonists in rats were examined. Phencyclidine, MK-801, and ketamine, noncompetitive NMDA-receptor antagonists, generalized to the discriminative stimulus effects of U-50,488H, but not those of TRK-820, whereas (±)-3-(2-carbaxypiperazine-4-yl) propyl-1-phosphonic acid (CPP), a competitive NMDA-receptor antagonist, and ifenprodil, an NR1 / NR2B NMDA-receptor antagonist, did not, suggesting that non-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…Furthermore, Killinger et al [409] demonstrated that the discriminative stimulus effects of salvinorin A do not generalize to LSD, another 5-HT receptor agonist. Others have reported that non-competitive NMDA receptor antagonists (ketamine, PCP, MK-801), but not competitive antagonists, generalize to the discriminative stimulus effects of U50,488, but not the KOR agonist TRK-820 [410]. Collectively, these findings suggest that psychomimetic effects produced by salvinorin A differ from those produced by classical hallucinogens.…”
Section: Csf and Tissue Levels Of Dyn In Schizophreniamentioning
confidence: 85%
“…Furthermore, Killinger et al [409] demonstrated that the discriminative stimulus effects of salvinorin A do not generalize to LSD, another 5-HT receptor agonist. Others have reported that non-competitive NMDA receptor antagonists (ketamine, PCP, MK-801), but not competitive antagonists, generalize to the discriminative stimulus effects of U50,488, but not the KOR agonist TRK-820 [410]. Collectively, these findings suggest that psychomimetic effects produced by salvinorin A differ from those produced by classical hallucinogens.…”
Section: Csf and Tissue Levels Of Dyn In Schizophreniamentioning
confidence: 85%
“…It also increases DA efflux in the NAc (Hancock and Stamford 1999), an effect often associated with reward and pleasure (Wise 2008). There is evidence in rats that ketamine and other non-competitive NMDA receptor antagonists (e.g., MK-801, phencyclidine) substitute for the KOR agonist U50,488 in drug discrimination tests (Mori et al 2006), suggesting similar discriminative stimulus properties in this species. It is conceivable that the drug discrimination test and the 5CSRTT are both most sensitive to the dissociative effects of these drugs in rats.…”
Section: Discussionmentioning
confidence: 99%
“…We previously demonstrated that the discriminative stimulus effects of the κ‐opioid receptor agonist U‐50,488H are associated with its aversive effects in rats (Mori et al, 2004). Moreover, we also reported that κ‐opioid receptor agonists, NMDA receptor antagonists and DA D 3 receptor agonists might possess similar discriminative stimulus effects in rats (Mori et al, 2006, Yoshizawa et al, 2010). Drug discrimination procedures have been shown to be useful for distinguishing drug effects mediated by κ‐opioid receptors from those mediated by other receptors and for characterizing and quantifying such drug‐receptor interactions (Teal and Holtzman, 1980; White and Holtzman, 1983), while its molecular signaling mechanism has not yet been characterized.…”
Section: Introductionmentioning
confidence: 79%
“…These data suggest that the κ‐opioid receptor is critical for the production of the U‐50,488H‐induced discriminative stimulus effect, as expected. We previously demonstrated that κ‐opioid receptor agonists, NMDA receptor antagonists and DA D 3 receptor agonists might possess similar discriminative stimulus effects in rats (Mori et al, 2006, Yoshizawa et al, 2010). However, we found in this study that the discriminative stimulus effects of U‐50,488H did not affect the mRNA expression of DA receptors and NMDA receptor subunits.…”
Section: Discussionmentioning
confidence: 97%